Can biochar alleviate soil compaction stress on wheat growth and mitigate soil N2O emissions? - Liu, Qi; Liu, Benjuan; Zhang, Yanhui; Lin, Zhibin; Zhu, Tongbin; Sun, Ruibo; Wang, Xiaojie; Ma, Jing; Bei, Qicheng; Liu, Gang; Lin, Xingwu; Xie, Zubin (Soil biology & biochemistry, 2017)
Soil compaction occurs widely in modern agriculture, leading to reduced crop yields and enhanced soil N2O emissions. Biochar, an emerging biomass-pyrolysis product with porous structure, is hypothesized to alleviate soil compaction problems. A field mesocosm experiment involving biochar addition and soil compaction in a factorial design was conducted on a land cultivated with wheat. The results showed that biochar had little effect on wheat grain yield, but it increased wheat vegetative growth and reduced seasonal cumulative soil N2O emissions from both compacted and non-compacted soils. Across all treatments, biochar-induced changes in individual soil N2O fluxes mainly occurred within a couple of days after nitrogen fertilization, and were sensitive to soil moisture, with an average increase of 13% under low soil moisture conditions (<70% water holding capacity (WHC)) that was likely driven by increased abundance of ammonia-oxidizing archaea and bacteria, and an average decrease of 36% under high soil moisture conditions (>70% WHC) that was likely induced by raised abundance of N2O-reducing bacteria. The stimulated population sizes of nitrifiers and denitrifiers in biochar-amended soils were more dependent on biochar's chemical mediation (a shift of soil pH from moderate acidity towards neutrality) than physical mediation. This study indicated that biochar could alleviate soil compaction stress on wheat growth and mitigate soil N2O emissions, and to promote biochar's role in reducing soil N2O emissions, the best practice for nitrogen fertilization is before precipitation or followed by irrigation. •Biochar alleviated soil-compaction induced negative physical effects.•Biochar increased wheat vegetative growth but not reproductive growth.•Biochar chemically-mediated effect dominated a rise in nitrifiers and denitrifiers.•Biochar impact on soil N2O flux was interactive with soil water and N fertilization.•Biochar can alleviate soil compaction stress on wheat growth and mitigate N2O flux.